Effects of aflatoxin B1 on growth performance, antioxidant status, immune response, and pro-inflammatory cytokine mRNA expression in ISA chicks - Hou, Lele; Qiu, Huiling; Li, Anping; Dong, Jihong; Zhu, Lianqin; Liu, Guowen; Chen, Fu (Frontiers in Veterinary Science, 2022)
The research evaluated the effects of Aflatoxin B1 on growth performance, antioxidant status, immune response, and pro-inflammatorycytokine mRNA expression in ISA chicks. 240 7-day-old ISA chicks were randomly assigned to four treatment groups. The control group comprised chicks fed a basal diet. The aflatoxin (AFB1)-treatment groups (T1, T2, and T3) comprised chicks fed the basal diet supplemented with AFB1 at concentrations of 5, 8, and 10 μg/kg, respectively. The growth performance, antioxidant status, immune responses, and pro-inflammatory cytokine mRNA expression in all groups were measured. In the T1 treatment group (receiving the lowest AFB1 dose), a reduction in the Newcastle disease virus antibody (NDV-Ab) titer, and increases in interleukin 2 , IL-6, and interferon γ mRNA levels were observed on days 21 and 42 (P < 0.05). Treatment with the higher AFB1 doses (groups T2 and T3) reduced the chicks’ growth performance on days 21 and 42, measured as reductions in body weight (BW) and average daily gain (ADG) compared with the control group. In the T2 and T3 groups, the total antioxidant capacity , glutathione peroxidase and superoxide dismutase activities, serum immunoglobulin A and IgG levels, and IL-2, IL-6, and IFN-γ levels were also lower than in the control group. On days 21 and 42, these two groups also showed increased malondialdehyde content, higher feed to gain ratio (F/G), and higher IL-2, IL-6, and IFN-γ mRNA levels than the control group (P < 0.05). The T2 and T3 groups also showed reduced T-AOC, NDV-Ab titer, IL-2 content, and GPx-1 mRNA levels on days 21 and 42 (P < 0.05), increased IL-6 and IFN-γ mRNA levels on day 21, and increased F/G and MDA content on day 42 (P < 0.05) compared with group (T1). Increased MDA content and IL-6 mRNA levels in the liver and ileum were observed in group T3 compared with group T2 on day 21, and lower IgM and IL-6 levels were observed on days 21 and 42 (P < 0.05). In conclusion, our data showed that AFB1 exposure resulted in dose-dependent oxidative and inflammatory damage, immunosuppression, and a decline in the growth performance of chicks.